Perbedaan Efektivitas Perawatan Payudara dan Pijat Oksitosin terhadap Kelancaran Pengeluaran ASI pada Ibu Postpartum - Irnawati Irnawati; Lili Purnama Sari (Sarana Ilmu Indonesia (salnesia), 2022)
The health and survival of mothers and babies is strongly influenced by various factors of midwifery services provided to mothers, children, families and communities. The purpose of this study was to determine the difference in the effectiveness of breast care and oxytocin massage on the smooth release of breast milk in postpartum mothers. The research method used comparative research with purposive sampling. The number of samples as many as 30 people. The results of this study indicated that there were differences in results between breast care and oxytocin massage on milk production, seen from a significant value of 0,000 (p<0,05). The conclusion in this study is that there is a difference between breast care and oxytocin massage for postpartum mothers at the Patingalloang Health Center.